Literature Review : The Influence of Promotional Media on Knowledge and Attitude to Prevent Diabetes Mellitus in Adolescents - Amalia, Ade Nurul; Tosepu, Ramadhan ((Jurnal Ilmiah Mahasiswa Kesehatan Masyarakat), 2024)
Diabetes is one of the four priority non-communicable diseases. According to the data, it is evident that 1 in 2 individuals with diabetes are unaware of their condition, while in fact, 80% of diabetes cases can be prevented. Referring to previous studies, both Type 1 and Type 2 diabetes are increasing among adolescents. Although the underlying pathophysiological mechanisms and clinical profiles differ, there are common principles in managing both types. These principles involve achieving adequate glycemic control and adopting a healthy lifestyle with the aim of preventing chronic diabetes-related complications. This research utilized a dataset consisting of journals focused on adolescent health as the study population. We identified 30 indexed journals from various publishers in this literature review. The databases used for the search include ProQuest, ScienceDirect, PubMed, and the National Library. The review was limited to research published in the last 5 years. As a result, thirty (30) journals covering a range of topics related to previous research, including: 1) Diabetes, 2) Health Promotion, 3) Promotional Media, 4) Knowledge and Attitudes, and 5) Adolescents, were reviewed. Keywords: Diabetes, Media Promotion, Health Promotion, Adolescents.